Microstructural Characterization and Evaluation of the Thermomechanical Behavior of an Al 7075-T651 Alloy Deformed by Two Passes of ECAP - Silva,Daniel Carvalho (2017)
Billets of an Al 7075-T651 alloy were processed by two passes of equal channel angular pressing, ECAP, by following route A. First pass was performed at 180°C and the second one in the temperatures 130 and 180°C. The resulting microstructures were characterized by optical microscopy, OM, and scanning electron microscopy, SEM. Also, material macroscopic mechanical properties were evaluated by performing uniaxial compression and Vickers microhardness tests. After the second pass, it was not verified a noticeable grain refinement. After second pass at 130ºC, the samples presented higher mechanical strength than observed after their processing at 180°C and the second pass resulted in a decrease in the mechanical properties compared to the deformation by one pass at 180°C.